Pendidikan Agama Islam dalam Membentuk Karakter Masyarakat - Pasaribu, Ikhlasul Amal; Solihin, Solihin; Harahap, Muhammad Rifi (Yayasan Rahmat Islamiyah, 2024)
Islamic religious education has a significant role in shaping the character of society. This research aims to explore the impact of Islamic religious education on the formation of individual and societal character. This research method uses a qualitative approach with data collection techniques through interviews, observation and document analysis. Respondents consisted of Islamic teachers, students and community leaders. The results of this survey provide a fairly optimistic picture of society's perceptions and expectations regarding the role of Islamic religious education in shaping the character of a responsible and civilized society. Nevertheless, efforts are still needed to continue to improve the quality of Islamic religious education so that it can have a greater impact in shaping the character of society. In conclusion, Islamic religious education has a vital role in forming ethical and good personality in society. Therefore, strengthening Islamic religious education needs to be intensified to create a harmonious and cultured society.